Scribal habits in Near Eastern manuscript traditions - Kiraz, George Anton; Schmidtke, Sabine (Texts and studies, 2021)
Most scholars who employ manuscripts in their research tend to focus on the literary content itself. But what about the role of the scribe who typically remains at the periphery of research? How can we, in the words of the NT textual critic James Royse, “virtually look over the scribe’s shoulder” to understand the process by which our manuscripts were produced? Moreover, manuscripts often contain far more material than the words that form their primary texts: dots and various other symbols that mark vowels (in the case of Semitic languages), intonation, readings aids, and other textual markers; marginal notes and sigla that provide additional explanatory content akin to but substantially different from our modern notes and endnotes; images and illustrations that present additional material not found in the main text. These extratextual (or peritextual) elements add additional layers to the main body of the text and are crucial for our understanding of the text’s transmission history as well as scribal habits. This volume brings together contributions by scholars focussing on such extra-, peritextual elements as found in Middle Eastern manuscripts written in Hebrew, Syriac, Arabic, Persian and other languages, to study the individuals who produced our manuscripts and how they shaped the transmission of literary texts they copied.